Characterization of Preoperative Anxiety and Its Influence on Postoperative Pain Scores in Adult Patients Undergoing Elective Surgical Procedures in a Tertiary Care Hospital - Zahid, Faiza; Zahid, Ahmad; Zahid, Abdullah; Inayat, Maryam (Biological and Clinical Sciences Research Journal, 2025)
Preoperative anxiety is a common psychological response among patients undergoing elective surgery and has been increasingly recognized as an important determinant of postoperative outcomes, particularly pain. Elevated anxiety levels prior to surgery may amplify pain perception and adversely affect recovery, yet data from low- and middle-income countries remain limited. Objective: To determine the prevalence of preoperative anxiety and evaluate its association with postoperative pain among adult patients undergoing elective surgical procedures at a tertiary care hospital in Pakistan. Methods: A descriptive case series was conducted at Doctors Hospital and Medical Center in Lahore from January to April 2025. A total of 100 adult patients aged 18–60 years scheduled for elective surgery under general anesthesia were enrolled using non-probability consecutive sampling. Preoperative anxiety was assessed using the State Anxiety Inventory Form Y-6, with scores >40 indicating clinically significant anxiety. Postoperative pain was measured using the Numeric Rating Scale at one and three hours after surgery. Associations were analyzed using chi-square testing, correlation measures, and binary logistic regression. Results: The mean age of participants was 39.8 ± 11.2 years, and 54% were female. Preoperative anxiety was present in 38% of patients. Postoperative pain was reported by 76.3% of anxious patients compared to 16.1% of non-anxious patients (χ² = 35.874, p < 0.001). A strong positive correlation was observed between preoperative anxiety and postoperative pain (Phi and Cramer's V = 0.599). Logistic regression demonstrated that preoperative anxiety was an independent predictor of postoperative pain, increasing the odds by approximately sixteen times (OR = 16.19, 95% CI: 5.56–47.15). Gender, body mass index, and marital status were not significant predictors. Conclusion: Preoperative anxiety is highly prevalent and strongly associated with postoperative pain among elective surgical patients Early identification and targeted management of anxiety may play a critical role in improving postoperative pain outcomes and overall recovery.